ANALISA EFEKTIFITAS POLA OPERASI MRT JAKARTA DENGAN HEADWAY 10 MENIT SAAT PANDEMI: ANALYSIS OF THE EFFECTIVENESS OF JAKARTA MRT OPERATING PATTERNS WITH 10 MINUTES HEADWAY DURING PANDEMIC - Sudarwati; Cirilus Panji Asmoro (FTSP Universitas Jayabaya, 2021)
MRT Jakarta is a new face of urban public transport in DKI Jakarta. It was start the commercial operation on March 2019, give a choice for Jakarta Citizen for using comfortable, safe and on time public transport. However, on march 2020 Indonesia Goverments announce about pandemic of Covid-19 and Indonesia have a new normal protocol for daily people movement. This has an impact on MRT Jakarta like decrease in the number of passanger. So we need the new analysis about Operation Pattern on MRT Jakarta. The purpose of this research is make a effective operation pattern of MRT Jakarta. With quantitative methodology, the data or information used is secondary data obtained from MRT Jakarta technical data and primary data obtained from direct observations in the field, and the result is based on maximum train occupancy, still enough for using 10 minutes headway and the operation start from 06:00 until 22:00.